Two-Dimensional Optical Metasurfaces: From Plasmons to Dielectrics - Bo Liu; Kerui Song; Jiangnan Xiao (Advances in Condensed Matter Physics)
Metasurfaces, kinds of planar ultrathin metamaterials, are able to modify the polarization, phase, and amplitude of physical fields of optical light by designed periodic subwavelength structures, attracting great interest in recent years. Based on the different type of the material, optical metasurfaces can be separated in two categories by the materials: one is metal and the other is dielectric. Metal metasurfaces rely on the surface plasma oscillations of subwavelength metal particles. Nevertheless, the loss caused by the metal structures has been a trouble, especially for devices working in transmit modes. The dielectric metasurfaces are based on the Faraday-Tyndall scattering of high-index dielectric light scattering particles. By reasonably designing the relevant parameters of the unit structure such as the size, direction, and shape, different functions of metasurfaces can realize and bring a wide range of applications. This article focuses on the metasurface concepts such as anomalous reflections and refractions and the working principle of different types of metasurfaces. Here, we briefly review the progress in developing optical over past few years and look into the near future.